Performance of the Cough and Sputum Assessment Questionnaire (CASA-Q) in COPD: Evidence from Clinical and Online Patient Interaction Studies - Patalano F; Hache C; Pethe A; Kaur H; Leidy NK; Arsiwala T; Afroz N; Gutzwiller FS (International Journal of COPD, 2022)
Francesco Patalano,1 Carolina Hache,2 Abhijit Pethe,3 Harneet Kaur,4 Nancy Kline Leidy,5 Tasneem Arsiwala,1 Nuzhat Afroz,6 Florian S Gutzwiller4 1Pediatric and Patient Reported Outcomes Center of Excellence, Novartis Pharma AG, Basel, Switzerland; 2Regulatory Affairs, Novartis Pharma AG, Basel, Switzerland; 3Biostatistics, Novartis Pharmaceuticals Corporation, East Hanover, NJ, USA; 4Global Access Evidence, Novartis Pharma AG, Basel, Switzerland; 5Patient-Centered Research, Evidera/PPD, Bethesda, MD, USA; 6Patient Access Services, Novartis Healthcare Pvt Ltd, Hyderabad, IndiaCorrespondence: Florian S Gutzwiller, HEOR & Access Evidence TA Head, Global Patient Access, Novartis Pharma AG, WSJ-188 6 001, Basel, CH-4056, Switzerland, Tel +41 616963713, Email florian.gutzwiller@novartis.comIntroduction: Patient perception of the burden of chronic bronchitis symptoms in chronic obstructive pulmonary disease (COPD) can be assessed using patient-reported outcome measures (PROMs). The Cough and Sputum Assessment Questionnaire (CASA-Q) was developed and tested for this purpose. This study reviewed the performance of the CASA-Q in published online studies and tested a novel approach to complement traditional methods of qualitative content validation.Methods: A targeted literature search was performed to identify published clinical studies of COPD using the CASA-Q as an endpoint. The performance of the questionnaire was examined in relation to other study endpoints, including clinical and functional measurements and other PROMs. Assessment of the content validity of the CASA-Q was carried out by comparing the content and structure of the questionnaire with published qualitative patient data from previously conducted online social media listening (SML) and online bulletin board (OBB) studies.Results: In the interventional clinical trials, CASA-Q change scores were consistent with study objectives and other endpoints, including FEV1 and other PROMs. Two observational studies showed cross-sectional correlations with other PROMs like the St.-George’s Respiratory Questionnaire (SGRQ) and COPD assessment test (CAT) scores. Qualitative data from the SML and OBB patient studies were consistent with the content and structure of the CASA-Q, supporting the content validity of the measure.Conclusion: Results suggest that the CASA-Q is appropriately responsive to changes in cough and sputum symptoms and clinical impact in trials of COPD. The mapping of qualitative findings from online SML and OBB studies to CASA-Q domains and items confirm the content validity of the instrument. These results suggest the CASA-Q can be a valuable tool for evaluating treatment effect in COPD trials.Keywords: patient-reported outcomes, social media, online bulletin board, online community, CASA-Q, chronic obstructive pulmonary disease, content validation, performance, chronic bronchitis